Electrical detection of spin-orbit torque in antiferromagnets - Göksal, Cemal İlkin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Ferromagnetic spintronics has been a game changer for memory technologies, until it has been understood that at some point ferromagnetic properties of these devices won’t be able to compensate for the demand on volume and performance. At this point, antiferromagnetic (AFM) spintronics emerged as the most promising alternative and this accelerated the research and investment on AFM spintronics. AFM materials are known with their magnetic toughness due to zero net magnetization in bulk and promising bit per volume ratio thanks to their two spin lattices pointing in opposite directions. In this study, our aim is to achieve current induced manipulation of antiferromagnetic moments. Though there are multiple suggested ways for AFM magnetization manipulation, we study DC electrical transport experiments where by we utilize spin-orbit torque (SOT) effect on metallic AFM materials (IrMn4,IrMn3FeMn). The underlying mechanism for spin manipulation is a mixture of Spin Hall Effect (SHE) and interfacial Rashba effect (IRE). We start our investigation with bi-layers of high SOC heavy metals (Pt, Ta) and AFM metal(IrMn4,FeMn) hetero structures of [HM/AFM]. Following these experiments, we also investigate the cumulative properties of SOT effect by demonstrating DC electrical transport experiments on HM/AFM/HM trilayer hetero structures and stacks of [HM/AFM/HM] × n, (where n=2,3,4 etc.). These results will help to improve understanding of the nature of electrical manipulation of AFM spin and determine the conditions to use them as spintronic devices.
Keywords: Ferromagnetic materials.; Antiferromagnetism.